Algae reactors for wastewater treatment - Whitton, Rachel Louise (Cranfield University, 2016)
The onset of the Water Framework Directive (WFD) will challenge water utilities to further reduce their wastewater phosphorus discharges to < 0.5 mg.L- 1 . Whilst conventional treatments, such as chemical dosing, are able to meet these new discharge consents, the strategies are representative of a linear economy model where resources are unrecovered and disposed. An alternative solution which can contribute to the aspiration of a circular economy is microalgae. Microalgae are ubiquitous in wastewater environments and assimilate phosphorus during their growth, to residual concentrations complementary of the WFD. Furthermore, microalgal biomass can be anaerobically digested to produce biomethane offering the potential for an energy neutral approach. However, uptake of microalgal systems are lacking in the UK through limited knowledge of operation; and the belief that such solutions are synonymous to large, shallow open ponds with extensive treatment times. The development of alternative microalgal reactors are increasingly investigated to overcome these implementation challenges. Of these, immobilised microalgae has shown great potential; and whilst within its infancy demonstrates the greatest opportunity for development and optimisation. This thesis determines the critical operational parameters that influence the remediation efficacy of immobilised microalgae for tertiary nutrient removal; including species selection, biomass concentration, treatment period and lighting; with recommendations for optimal performance. These recommendations are then applied to the design and operation of an immobilised bioreactor (IBR) to understand the key design and operating components that influence the overall economic viability. In doing so, the potential for an IBR to be economically viable, within the next decade, in comparison to traditional approaches are discussed.
Keywords: immobilisation; phosphate; nitrogen; circular economy